Can theory of mind deficits be measured reliably in people with mild and moderate Alzheimer’s dementia? - Choong, Caroline S.M.; Doody, Gillian A. (BioMed Central, 2013)
Background Patients suffering from Alzheimer’s dementia develop difficulties in social functioning. This has led to an interest in the study of “theory of mind” in this population. However, difficulty has arisen because the associated cognitive demands of traditional short story theory of mind assessments result in failure per se in this population, making it challenging to test pure theory of mind ability.